Joseph’s Food Politics as Life-Keeper of Many People: A Close Rereading of Genesis 47:13–26 - Karman, Yonky (Veritas : Jurnal Teologi dan Pelayanan, 2021)
The Septuagint reading predominantly influences the interpretation of Genesis 47:13-26 (primarily v. 21). Despite a positive portrayal of Joseph, he is also seen as Pharaoh’s accomplice to enslave the Egyptian people. This connection with slavery activities contradicts the traditional image of Joseph as the life-keeper of many people. Solution for the negative portrait of Joseph usually refers to the Masoretic Text, although it is not a reference to many modern Bible translations and commentaries. The Septuagint as a reference, in this case, is indeed difficult to reject. However, that does not mean that Joseph promotes the slavery of the Egyptian people throughout the land, but rather an ancient form of state capitalism. This article draws on textual criticism, word studies, form criticism, and agricultural knowledge background in the ancient Middle East. The contribution of this research is to show that, instead of enslaving, Joseph formulated an Egyptian food politics in the larger context of Joseph’s narrative reality as the life-keeper of many people.